How Joint Enterprise Liability Neutered the Criminal Cases Review Commission in England - Hewitt, Louise (The Wrongful Conviction Law Review, 2023)
In 2016 the English Supreme Court corrected the law concerning joint enterprise liablity in R v Jogee ([2016] UKSC 8). The decision did not invalidate every conviction made under the erroneous, albeit faithful application of the old law, on the basis it could lead to an unmanageable number of appeals. Individuals convicted as secondary parties prior to Jogee who appeal outside of the statutory 28 days have to demonstrate they have suffered a substantial injustice, the test imposed by the Court of Appeal in all change of (common) law cases. The Court of Appeal will also apply this test to a referral made by the English Crimial Cases Review Commission (CCRC). This has meant that the CCRC has no choice for this category of applicant, but to apply its own statutory test and also the substantial injustice test. The CCRC’s statutory real possibility test has been criticised for compromising its independence, on the basis the language makes it subordinate to the Court of Appeal. The fact that the CCRC has to apply the Court of Appeal’s substantial injustice test further questions just how subservient it is to the Court.This article is based on a research study produced by the author, which was the first to examine applications made to the CCRC from individuals who have been convicted under joint enterprise liability. The findings explore the extent to which the corrected law from Jogee is used in applications, and shows the limiting effect that the substantial injustice test has had on the CCRC. The study also reveals the low number of applicants identifying as Black British, despite existing research suggesting this demographic has the highest conviction rate for joint enterprise.